2021
DOI: 10.1177/09636897211036004
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Cryopreservation Does Not Affect Quality of Peripheral Blood Stem Cell Grafts: A Comparative Study of Native, Short-Term and Long-Term Cryopreserved Haematopoietic Stem Cells

Abstract: Cryopreserved haematopoietic progenitor cells are used to restore autologous haematopoiesis after high dose chemotherapy. Although the cells are routinely stored for a long period, concerns remain about the maximum storage time and the possible negative effect of storage on their potency. We evaluated the effect of cryopreservation on the quality of peripheral stem cell grafts stored for a short (3 months) and a long (10 years) period and we compared it to native products.The viability of CD34+ cells remained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…These low-molecular-weight cryoprotectants were originally discovered over 60 years ago 5 , 6 (not rationally selected for a particular biological/physical property), yet they have been exceptionally effective and widely used in both research and clinical applications. Stocks of red blood cells are cryopreserved using 20–40 wt% glycerol 7 , immortalized cell lines are routinely stored in 10% (v/v) DMSO and cells for clinical transplantation, including haematopoietic stem cells and chimeric antigen receptor (CAR)-T cells, are frequently cryopreserved in 5–10% DMSO 8 , 9 (amongst other additives).…”
Section: Introductionmentioning
confidence: 99%
“…These low-molecular-weight cryoprotectants were originally discovered over 60 years ago 5 , 6 (not rationally selected for a particular biological/physical property), yet they have been exceptionally effective and widely used in both research and clinical applications. Stocks of red blood cells are cryopreserved using 20–40 wt% glycerol 7 , immortalized cell lines are routinely stored in 10% (v/v) DMSO and cells for clinical transplantation, including haematopoietic stem cells and chimeric antigen receptor (CAR)-T cells, are frequently cryopreserved in 5–10% DMSO 8 , 9 (amongst other additives).…”
Section: Introductionmentioning
confidence: 99%
“…Even though the maximum duration of cryopreservation of HSPC products in our survey was 2.1 years, retention samples were cryopreserved significantly longer. However, previous studies have demonstrated that cryostorage has no clinically relevant negative effect on stem cell quality and potency, even after an extended period of more than 10 years [ 12 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most cryopreserved allogenic stem cell products are usually infused within months from harvesting, minimizing the possible additional detrimental effect of long storage on CD34+ quality. Moreover, most of the loss of CD34+ cells tend to occur during pre-storage manipulation and subsequent thawing, as storage for up to 10 years does not significantly affect the number, viability, metabolic function, and clonogenic potential of hematopoietic stem cells [ 53 ]. On the other side, for allogenic products, a significant amount of time may elapse between donation and cryopreservation.…”
Section: Cryopreservation Of Hematopoietic Stem Cell Graftsmentioning
confidence: 99%